Implementing an integrated diabetic foot care programme in Ireland: podiatrists' experience - Jennifer A. Pallin; Karen Buckley-O'Farrell; Fiona Riordan; Niamh McGrath; Kate O'Neill; Doireann MacLoughlin; Sean F. Dinneen; Claire M. Buckley; Sheena McHugh; Patricia M. Kearney (BMC, 2023)
Abstract Background International evidence suggests that an integrated multidisciplinary approach to diabetic foot management is necessary to prevent ulceration and progression to amputation. Many health systems have introduced policies or models of care supporting the introduction of this evidence into practice, but little is known about the experiences of those involved in implementation. This study addresses this gap by examining the experiences of podiatrists providing integrated diabetic foot care. Methods Between October 2017 and April 2018, an online survey comprising closed and open-ended questions on podiatrists' demographics, clinical activity, links with other services, continuous professional development activities and experiences of implementing the Model of Care was administered to podiatrists (n = 73) working for Ireland's Health Service Executive in the community and hospital setting. Data were analysed using descriptive statistics and qualitative content analysis. Results The response rate was 68% (n = 50), with 46% (n = 23), 38% (n = 19) and 16% (n = 8) working across hospital, community and both settings, respectively. Most reported treating high-risk patients (66%), those with active foot disease (61%) and educating people about the risk of diabetes to the lower limb (80%). Reported challenges towards integrated diabetic foot care include a perceived lack of awareness of the role of podiatry amongst other healthcare professionals, poor integration between hospital and community podiatry services, especially where new services had been developed, and insufficient number of podiatrists to meet service demands. Conclusion Previous evidence has shown that there is often a gap between what is set out by a policy and what it looks like when delivered to service users. Results from the current study support this, highlighting that while most podiatrists work in line with national recommendations, there are specific gaps and challenges that need to be addressed to ensure successful policy implementation.